2005
DOI: 10.1677/joe.1.05916
|View full text |Cite
|
Sign up to set email alerts
|

Nestin expression and clonal analysis of islet-derived epithelial monolayers: insight into nestin-expressing cell heterogeneity and differentiation potential

Abstract: There has over the last several years been renewed interest in developing a system for generating new islets and a search for a self-renewing population in the pancreas. In particular, the neural stem cell marker nestin has been implicated as an islet precursor marker and its immunoreactivity has been localized in the islets of Langerhans. This study examines islet-derived epithelial monolayers expanded ex vivo to provide a source of nestin-expressing progenitor cells -a model that will help us understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…Our results have shown that almost all PDX1 + cells present at the end of hEB formation produce NES, but these cells later become heterogeneous (PDX1 + NES + , PDX1 − NES + , and PDX1 + NES − ). Similarly, a recent study using clonal analysis showed that NES + populations from the postnatal rat pancreatic islet were heterogeneous, but a small proportion of the NES + cells produced PDX1, and suggested that the NES + PDX1 + population may play a role in islet formation [47]. However, it remains unclear whether the PDX1 + cells producing NES in our system gave rise to pancreatic endocrine cells, exocrine cells or other cell types after transplantation.…”
Section: Discussionsupporting
confidence: 52%
“…Our results have shown that almost all PDX1 + cells present at the end of hEB formation produce NES, but these cells later become heterogeneous (PDX1 + NES + , PDX1 − NES + , and PDX1 + NES − ). Similarly, a recent study using clonal analysis showed that NES + populations from the postnatal rat pancreatic islet were heterogeneous, but a small proportion of the NES + cells produced PDX1, and suggested that the NES + PDX1 + population may play a role in islet formation [47]. However, it remains unclear whether the PDX1 + cells producing NES in our system gave rise to pancreatic endocrine cells, exocrine cells or other cell types after transplantation.…”
Section: Discussionsupporting
confidence: 52%
“…36 In similar lines, the role of nestin has also been advocated in the process of cellular rearrangements 37,38 and the renewal capacity of NPC to differentiate into insulin and glucagon positive cells have been reported in human islet explants, rat pancreatic tissue and embryonic stem cells. 39,40 The varied expression and characterization of NPC in different cell types is thought to have considerable functional significance during the developmental process. Nestin was viewed as the intra islet cell precursor, but lineage tracing analysis did not document for this.…”
Section: Islet Progenitors From Endocrine Pancreasmentioning
confidence: 99%
“…. Some nestin-positive cells found in cultures of rodent islets expressed PDX-1 and were able to re-express insulin at the mRNA and protein level [16]. Culture of islet-like cell clusters from human fetal pancreas developed into monolayer epithelial-like cells with high proliferative potential, and these cells, expressing both nestin and ABCG2 stem cell markers, differentiated into insulin-positive cells [17].…”
Section: Other Potential Progenitor Cellsmentioning
confidence: 99%